Measuring muscle tone with isokinetic dynamometer technique in stroke patients - Dehno Nasrin Salehi; Sarvestani Fahimeh Kamali; Shariat Abdolhamid; Jaberzadeh Shapour (Sciendo, 2019)
Study aim: Increased muscle tone, a common consequence of stroke, has neural and non-neural components. Spasticity is related to the neural component. Non-neural resistance arises from passive stiffness. This study was designed to assess the feasibility of using isokinetic dynamometry to evaluate wrist flexor muscle spasticity in stroke patients.